Datasets:

Modalities:
Text
Languages:
English
Libraries:
Datasets
License:
Zhangir Azerbayev
squashed?
4365a98
raw
history blame
5.47 kB
(* ======== Robbins Conjecture proof from John ============================= *)
hide_constant "+";;
horizon := 0;;
timeout := 2;; (* John apparently has a faster computer :-) *)
let ROBBINS = thm `;
let (+) be A->A->A;
let n be A->A;
assume !x y. x+y = y+x [COM];
assume !x y z. x+(y+z) = (x+y)+z [ASS];
assume !a b. n(n(a+b)+n(a+n(b))) = a [ROB];
consider x such that x:A = x;
set u = n(x+n(x)) [U];
set d = x+u [D];
set c = x+x+x+u [C];
set j = n(c+d) [J];
set e = u+n(x+x)+n(c) [E];
n(u+n(x+x)) = x [0]
proof n(u+n(x+x))
= n(n(x+n(x))+n(x+x)) by U;
.= x by ROB,COM;
qed by -;
n(x+u+n(x+u+n(x+x)+n(c))) = n(c) [1]
proof n(x+u+n(x+u+n(x+x)+n(c)))
= n((x+u)+n(x+u+n(x+x)+n(c))) by ASS,COM;
.= n(n(n((x+u)+x+x)+n((x+u)+n(x+x)))+n(x+u+n(x+x)+n(c))) by ROB;
.= n(n(n(x+u+x+x)+n(x+u+n(x+x)))+n(x+u+n(x+x)+n(c))) by ASS;
.= n(n(n(x+x+x+u)+n(x+u+n(x+x)))+n(x+u+n(x+x)+n(c))) by ASS,COM; // slow
.= n(n(n(c)+n(x+u+n(x+x)))+n(n(c)+x+u+n(x+x))) by ASS,COM,C;
.= n(c) by ROB,ASS,COM;
qed by -;
n(u+n(c)) = x [2]
proof n(u+n(c))
= n(u+n(x+x+u+x)) by C,ASS,COM;
.= n(u+n(x+x+u+n(u+n(x+x)))) by 0;
.= n(n(n(u+x+x)+n(u+n(x+x)))+n(x+x+u+n(u+n(x+x)))) by ROB;
.= n(n(x+x+u+n(u+n(x+x)))+n(n(u+x+x)+n(u+n(x+x)))) by COM;
.= n(n((x+x+u)+n(u+n(x+x)))+n(n(u+x+x)+n(u+n(x+x)))) by ASS;
.= n(n(n(u+n(x+x))+u+x+x)+n(n(u+n(x+x))+n(u+x+x))) by ASS,COM;
.= n(u+n(x+x)) by ROB;
.= x by 0;
qed by -;
n(j+u) = x [3]
proof n(j+u)
= n(n(x+c+u)+u) by J,D,COM,ASS;
.= n(n(x+c+u)+n(n(u+c)+n(u+n(c)))) by ROB;
.= n(n(x+c+u)+n(x+n(c+u))) by 2,COM;
.= x by ROB;
qed by -;
n(x+n(x+n(x+x)+u+n(c))) = n(x+x) [4]
proof n(x+n(x+n(x+x)+u+n(c)))
= n(n(n(x+n(u+n(c)))+n(x+u+n(c)))+n(x+n(x+x)+u+n(c)))
by ROB,ASS,COM;
.= n(n(n(x+x)+n(x+u+n(c)))+n(n(x+x)+x+u+n(c))) by 2,ASS,COM;
.= n(n(n(x+x)+x+u+n(c))+n(n(x+x)+n(x+u+n(c)))) by ASS,COM;
.= n(x+x) by ROB,COM;
qed by -;
n(x+n(c)) = u [5]
proof n(x+n(c))
= n(x+n(x+u+n(x+u+n(x+x)+n(c)))) by 1;
.= n(n(u+n(x+x))+n(x+u+n(x+u+n(x+x)+n(c)))) by 0;
.= n(n(u+n(x+x))+n(u+x+n(x+e))) by E,COM,ASS;
.= n(n(u+n(x+n(x+n(x+x)+u+n(c))))+n(u+x+n(x+e))) by 4;
.= n(n(u+n(x+n(x+(u+n(c))+n(x+x))))+n(u+x+n(x+e))) by COM;
.= n(n(u+n(x+n(x+u+n(c)+n(x+x))))+n(u+x+n(x+e))) by ASS;
.= n(n(u+n(x+n(x+u+n(x+x)+n(c))))+n(u+x+n(x+e))) by COM;
.= n(n(u+n(x+n(x+e)))+n(u+x+n(x+e))) by E;
.= u by ROB,COM;
qed by -;
n(j+x) = u [6]
proof n(j+x)
= n(j+n(n(x+c)+n(x+n(c)))) by ROB;
.= n(j+n(n(x+c)+u)) by 5;
.= n(n(u+x+c)+n(u+n(x+c))) by J,D,COM,ASS;
.= u by ROB;
qed by -;
n(c+d) = n(c)
proof n(c+d)
= j by J;
.= n(n(j+n(x+n(c)))+n(j+x+n(c))) by ROB,COM;
.= n(n(j+u)+n(j+x+n(c))) by 5;
.= n(x+n(j+x+n(c))) by 3;
.= n(n(n(c)+u)+n(n(c)+j+x)) by 2,COM,ASS;
.= n(n(n(c)+n(j+x))+n(n(c)+j+x)) by 6;
.= n(c) by ROB,COM;
qed by -;
thus ?c d. n(c+d) = n(c) by -`;;
timeout := 1;;
(* ======== REWRITE version ================================================ *)
let old_default_prover = !default_prover;;
default_prover := "REWRITE_TAC",REWRITE_TAC;;
let ROBBINS = thm `;
let (+) be A->A->A;
let n be A->A;
assume !x y. x+y = y+x [COM];
assume !x y z. x+(y+z) = (x+y)+z [ASS];
assume !a b. n(n(a+b)+n(a+n(b))) = a [ROB];
!x y z. x+y = y+x /\ (x+y)+z = x+(y+z) /\ x+(y+z) = y+(x+z) [AC]
by MESON_TAC,COM,ASS;
consider x such that x:A = x;
set u = n(x+n(x)) [U];
set d = x+u [D];
set c = x+x+x+u [C];
set j = n(c+d) [J];
set e = u+n(x+x)+n(c) [E];
n(u+n(x+x)) = x [0]
proof n(u+n(x+x))
= n(n(x+x)+n(x+n(x))) by U,AC;
.= x by ROB;
qed by -;
n(x+u+n(x+u+n(x+x)+n(c))) = n(c) [1]
proof n(x+u+n(x+u+n(x+x)+n(c)))
= n((x+u)+n(x+u+n(x+x)+n(c))) by AC;
.= n(n(n((x+u)+x+x)+n((x+u)+n(x+x)))+n(x+u+n(x+x)+n(c))) by ROB;
.= n(n(n(c)+x+u+n(x+x))+n(n(c)+n(x+u+n(x+x)))) by C,AC;
.= n(c) by ROB;
qed by -;
n(u+n(c)) = x [2]
proof n(u+n(c))
= n(u+n(x+x+u+n(u+n(x+x)))) by 0,C,AC;
.= n(n(n(u+x+x)+n(u+n(x+x)))+n(x+x+u+n(u+n(x+x)))) by ROB;
.= n(n(n(u+n(x+x))+u+x+x)+n(n(u+n(x+x))+n(u+x+x))) by AC;
.= n(u+n(x+x)) by ROB;
.= x by 0;
qed by -;
n(j+u) = x [3]
proof n(j+u)
= n(n(x+c+u)+u) by J,D,AC;
.= n(n(x+c+u)+n(n(u+c)+n(u+n(c)))) by ROB;
.= n(n(x+c+u)+n(x+n(c+u))) by 2,AC;
.= x by ROB;
qed by -;
n(x+n(x+n(x+x)+u+n(c))) = n(x+x) [4]
proof n(x+n(x+n(x+x)+u+n(c)))
= n(n(n(x+u+n(c))+n(x+n(u+n(c))))+n(x+n(x+x)+u+n(c))) by ROB;
.= n(n(n(x+x)+x+u+n(c))+n(n(x+x)+n(x+u+n(c)))) by 2,AC;
.= n(x+x) by ROB;
qed by -;
n(x+n(c)) = u [5]
proof n(x+n(c))
= n(n(u+n(x+x))+n(x+u+n(x+u+n(x+x)+n(c)))) by 0,1;
.= n(n(u+n(x+n(x+n(x+x)+u+n(c))))+n(u+x+n(x+e))) by 4,E,AC;
.= n(n(u+x+n(x+e))+n(u+n(x+n(x+e)))) by E,AC;
.= u by ROB;
qed by -;
n(j+x) = u [6]
proof n(j+x)
= n(j+n(n(x+c)+n(x+n(c)))) by ROB;
.= n(n(u+x+c)+n(u+n(x+c))) by 5,J,D,AC;
.= u by ROB;
qed by -;
n(c+d) = n(c)
proof n(c+d)
= j by J;
.= n(n(j+x+n(c))+n(j+n(x+n(c)))) by ROB;
.= n(n(u+n(c))+n(j+x+n(c))) by 2,3,5,AC;
.= n(n(n(c)+j+x)+n(n(c)+n(j+x))) by 6,AC;
.= n(c) by ROB;
qed by -;
thus ?c d. n(c+d) = n(c) by MESON_TAC,-`;;
unhide_constant "+";;
default_prover := old_default_prover;;